2020
DOI: 10.1007/s00261-020-02669-2
|View full text |Cite
|
Sign up to set email alerts
|

Abdominopelvic CT findings in patients with novel coronavirus disease 2019 (COVID-19)

Abstract: Purpose Some patients with novel coronavirus disease 2019 (COVID-2019) present with abdominal symptoms. Abdominal manifestations of COVID on imaging are not yet established. The goal of this study was to quantify the frequency of positive findings on abdominopelvic CT in COVID-positive patients, and to identify clinical factors associated with positive findings to assist with imaging triage. Materials and methods This retrospective study included adult COVID-positive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
68
2
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 24 publications
10
68
2
9
Order By: Relevance
“…The findings in our study are in partial agreement with two recently published studies [ 12 , 13 ]. Similar to the study by Goldberg-Stein et al and Bhayana et al [ 12 , 13 ], the most common abdominal finding in our study was in the GI tract with fluid-filled colon being the most common finding.…”
Section: Discussionsupporting
confidence: 94%
“…The findings in our study are in partial agreement with two recently published studies [ 12 , 13 ]. Similar to the study by Goldberg-Stein et al and Bhayana et al [ 12 , 13 ], the most common abdominal finding in our study was in the GI tract with fluid-filled colon being the most common finding.…”
Section: Discussionsupporting
confidence: 94%
“…Only three (7%) patients showed CT findings of a nonspecific enteritis, with pneumatosis intestinalis present on one scan, and no findings of portal venous gas. Our results are more similar to Goldberg-Stein et al [15] who also found that gastrointestinal tract findings were the most common category of abnormality on abdominal CTs (31.2%), but with wall thickening being less common (15%) and no reported cases of pneumatosis or portal venous gas. Another study [9] of 23 patients with lung base findings suspicious for COVID-19 infection reported a variety of typical findings characteristic of pre-COVID-19 abdominal pain diagnoses, with no abnormalities of the luminal gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 91%
“…Pre-pandemic reports have assessed the value of close examination of the lung bases for clinically significant abnormalities [16]. Our study, and others [8][9][10]15], show that lung base abnormalities on abdominal CT may now include findings that suggest a diagnosis of COVID-19 disease in a substantial percentage of cases.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…When abdominal pathology is present, the bowel is often affected. Goldberg-Stein et al reported abdominal pelvic pathology in 57% of COVID-19 positive patients with 31% showing GI tract abnormalities [12]. Bhayana et al found 31% of CT scans had bowel pathology in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%